Time and Antigen-Stimulation History Influence Memory CD8 T Cell Bystander Responses - Martin, Matthew D.; Shan, Qiang; Xue, Hai-Hui; Badovinac, Vladimir P. (Frontiers in Immunology, 2017)
Memory CD8 T cells can be activated and induced to produce cytokines and increase stores of cytolytic proteins not only in response to cognate antigen (Ag), but also in response to inflammatory cytokines (bystander responses). Importantly, bystander memory CD8 T cell functions have been shown to be dependent upon memory CD8 T cell fitness, since exhausted CD8 T cells have diminished capacity to respond to inflammatory cues. While it is known that memory CD8 T cell functional abilities, including ability to produce cytokines in response to cognate Ag, change with time after initial Ag encounter and upon multiple Ag-stimulations (e.g. primary vs. tertiary CD8 T cell responses), it is unknown if bystander memory CD8 T cell responses are influenced by time or by Ag-exposure history. Here, we examined time and Ag-stimulation history-dependent alterations in virus-specific memory CD8 T cell bystander functions in response to inflammatory cytokines and unrelated bacterial infection. We found that expression of cytokine receptors and ability to produce IFN- following heterologous infection or incubation with inflammatory cytokines decreases with time following initial Ag encounter and increases with additional Ag encounters, suggesting that the ability to sense inflammation and respond with bystander cytokine production is dependent on age and Ag-stimulation history of memory CD8 T cells. These data shed further light on the regulation of memory CD8 T cell effector functions and have important implications for the development of vaccines designed to elicit protective memory CD8 T cells.